Chatbot for education - Chan, Zavier Li Wei (Nanyang Technological University, 2024)
Chatbots have emerged as a promising technology for enhancing education and supporting students' learning experiences across various disciplines. By leveraging natural language processing and machine learning techniques, chatbots can engage in human-like conversations, providing personalized assistance, answering questions, and guiding learners through educational content. The integration of chatbots in educational settings offers several potential benefits, including increased accessibility to learning resources, real-time feedback and support, and the ability to cater to diverse learning styles and preferences.